How Implementing a Quality Management System at the LIONS Eye Bank Saar-Lor-Lux, Trier/Western Palatinate from 2006 to 2016 Impacted the Rate and Reasons for Discarding Human Organ-Cultured Corneas - Laun, Daniel; Suffo, Shady; Kramp, Kristina; Bischoff, Mona; Huber, Manuela; Langenbucher, Achim; Seitz, Berthold (Klinische Monatsblätter für Augenheilkunde, 2021)
Background The aim of this study was to explore how the implementation of the quality management system (QM; according to DIN EN ISO 9001 : 2008) at the LIONS Eye Bank impacted the rate and reasons for discarding donated corneas. The QM system was introduced in November 2010.Material and methods The rate of and reasons for discarding cornea tissues at the LIONS Eye Bank Saar-Lor-Lux,Trier/Western Palatinate from 2006 to 2016 were analysed retrospectively. 4,140 corneas from 2,084 donors were analysed. 1,640 corneas were processed before the QM system had been introduced and 2,500 corneas thereafter. Main reasons for discarding cornea tissues were endothelial quality, contamination of the medium and a positive conjunctival swab. The data was extracted from clinical files and data filing systems, entered into a Microsoft Access database and analysed statistically with SPSS.Outcome Following the implementation of a QM system, the discard rate decreased significantly from 50.1% to 39.7% (p < 0.0001). Prior to the implementation of the QM system, 493 (30.1%) cornea tissues had been discarded due to endothelial quality, while this figure improved significantly to 604 (24.2%) after the QM system had been implemented (p < 0.0001). Contamination was the reason for discarding tissue in 173 (10.5%) cases before implementation of the QM system, and in 124 (5.0%) cases thereafter (p < 0.0001). Positive conjunctival swab was the reason for discarding tissue in 10 (0.6%) cases before the QM system had been implemented, and in 53 (2.1%) cases thereafter (p < 0.0001).Conclusion Implementation of a QM system significantly reduced the rate of discarded donor tissue in the LIONS Eye Bank. Better management of contamination as a reason for discarding cornea tissues can be attributed to improved standards, protocols and training that are part of this QM system.Hintergrund Ziel dieser Studie war es, den Einfluss der Einführung des QM-Systems (QM: Qualitätsmanagement, nach DIN EN ISO 9001 : 2008) auf die Verwerfungsrate und -gründe von Spendergewebe in einer Hornhautbank zu erforschen. Die Einführung des QM-Systems erfolgte im November 2010.Material und Methoden Die Verwerfungsrate und -gründe wurden retrospektiv für die Jahre 2006 bis 2016 in der LIONS-Hornhautbank Saar-Lor-Lux, Trier/Westpfalz des Universitätsklinikums des Saarlandes (UKS) analysiert. 4140 Hornhäute von 2084 Spendern wurden einbezogen. 1640 Hornhäute entstammten der Zeit vor Einführung des zertifizierten QM-Systems (nach DIN EN ISO 9001 : 2008) und 2500 Hornhäute nach Einführung. Bei den analysierten Verwerfungsgründen handelte es sich um die Endothelqualität, Kontamination des Mediums und der positiven Bindehautabstriche. Die Daten der Spender und Hornhäute wurden aus klinikinternen Dokumenten und Systemen in eine Microsoft-Access-Datenbank übertragen und mittels SPSS statistisch ausgewertet.Ergebnisse Nach Einführung des QM-Systems sank die Verwerfungsrate von 50,1 auf 39,7% (p < 0,0001). Vor der Einführung wurden 493 (30,1%) der Hornhäute aufgrund der Endothelqualität verworfen, nach der Einführung waren es 604 (24,2%) (p < 0,0001). Aufgrund einer Kontamination wurden vor Einführung 173 (10,5%) Hornhäute und nach Einführung 124 (5,0%) verworfen (p < 0,0001). Wegen des Bindehautabstriches wurden vor Einführung 10 (0,6%) und nach Einführung 53 (2,1%) verworfen (p < 0,0001).Schlussfolgerung Die Verwerfungsrate in der LIONS-Hornhautbank konnte nach Einführung des QM-Systems signifikant gesenkt werden. Durch vermehrte Mitarbeiterschulungen sowie durch einheitliche und höhere Standards des QM-Systems bez. Ablauf der Entnahme und Kultivierung konnte die Kontaminationsrate signifikant reduziert werden.
Keywords: cornea; eye bank; cornea donor; quality management system